Influence of Spanish TV commercials on child obesity. Issue 6 (June 2015) - Ramos, C.; Navas, J.
Abstract Objectives To examine the strategies used in food advertising campaigns on Spanish television and their breach of the Self-Regulation Code on Food Advertising aimed at Preventing Obesity and Promoting Healthy Habits in Children, as such breach advocates the consumption of products that fail to meet the nutritional requirements. Study design Observational descriptive study. Methods Viewing and content analysis of 52 food commercials on the children's television channels 'Disney Channel' and 'Boing' on Saturday and Sunday (9:00–12:00) and general channels 'Telecinco' and 'Antena 3' on Monday to Friday (8:00–9:00 and 17:00–20:00), from March to May 2013; subsequent analysis of the nutrition labelling of the advertised products. Results There are different ways of bypassing the advertising agreement. Strategies are used which hide or distort the facts about the product in favour of the advertiser. 18 advertisements refer to website or Facebook pages, thus facilitating feedback, and 11 advertisements refer to the Plan for Promoting Healthy Lifestyles in the Spanish Population. With regard to nutritional quality, the composition of the products analysed is high in sugars and saturated fats with average levels of fat and salt. A comparison of the broadcast time of the commercials shows that the figures for fat and saturated fat are similar in food advertised in the morning and in the afternoon, but products that are high in sugar and salt are advertised more in the morning. If the overall figures are compared, they are higher in foods advertised in the morning. Discussion The Self-Regulation Code is insufficient. There is an obvious risk of trivialising the messages of the health promotion plan. The regulation of advertising is complex and if the nutritional composition of the foods advertised is likely to lead to child obesity, it is essential to reflect on the consequences deriving from the advertising of these products.